Social Security Measures And Their Implementation In Selected Industries Of Malaysia - Panda, Sitansu; Khan, M. (2017)
Malaysia is one of the leading economies in the world which has been striving to develop its human capital in order to attain the National Transformation Policy 2050 (TN50). This country has been ranked 62nd among 187 countries based on the Human Development Index (HDI) in 2015 and is being ranked at 47 among 157 countries as far as the United Nation's World Happiness Index study in 2016 is concerned. Some of the areas like higher education, skill development, technological innovation, building infrastructure; and transportation projects for infrastructure development have been undertaken. All the progress depends on the utilization of the human capital and their effective management. Maintaining sound employment · relationship among different stakeholders especially the employer and employees is vital for attaining planned policy goals.